Foreign bodies in the oesophagus - surgery for failed endoscopic retrieval - Pillai, Sastha Ahanatha; A., Sivasankar; T., Selvaraj (International Surgery Journal, 2016)
Background:Foreign body (FB) ingestion is common in children, but frequently seen in adults. Most of the ingested foreign bodies pass spontaneously. Sharp FBs can perforate the oesophagus or get impacted. FBs retained in the oesophagus need to be removed. Methods: The aim of the study was to analyse the symptoms, management and outcome of patients presenting with foreign bodies in the oesophagus. All patients who presented with a retained FB in the oesophagus between September 2013 and August 2015 were included in the study. Results:There were 27 patients with foreign bodies retained in the oesophagus. In 22 patients the foreign bodies were removed using an upper GI endoscope. In 5 patients the foreign bodies were impacted in the oesophagus and endoscopic removal failed. These patients required surgical removal. In 3 patients it was removed by a cervical approach and 2 patients required a thoracotomy. Two patients developed post-surgical leak. Both these patients had presented more than 24 hours after ingestion. There was no mortality. Conclusions:Delayed presentation is associated with a higher risk of leak and complications. Early diagnosis and immediate removal is important to avoid complications. A multidisciplinary approach is needed to manage these patients.